Post‐Fundoplication Dumping Syndrome: A Frequent "Rare" Complication. Issue 1 (2018) - Kataria, Rahul; Linn, Sandar; Malik, Zubair; Abbas, Abbas E.; Parkman, Henry; Schey, Ron
ABSTRACT : N/A: Gastroparesis, caused by delayed emptying of the stomach, has been shown to be associated with Nissen fundoplication. However, symptomatic rapid emptying of the stomach is rare after Nissen fundoplication, and its treatment is often challenging. We report 2 patients with dumping‐like syndrome post‐fundoplication with marked improvement of symptoms after dietary management and medical treatment.